Inventarisasi Kepiting Air Tawar (Brachyura) di Cabang Panti Taman Nasional Gunung Palung Kalimantan Barat - Tri Rima Setyawati, Ina Idola Junardi (Universitas Tanjungpura, 2018)
Freshwater crabs have an important role in maintaining the balance of the ecosystem. The purpose of research is to know the freshwater crabs and habitat characteristics of Cabang Panti Research Station in Gunung Palung National Park, Kayong Utara Regency. We use a purposive Random sampling and hand collecting methods to inventory of the freshwater crabs. The Cabang Panti Research Station has a three species of freshwater crabs, namely Parathelphusa maindroni, Terrathelphusa sp. and Isolapoamon spatha. Parahelphusa maindroni is the most abundance in freshwater swamps and alluvial habitat.